Certain Integrals Arising from Ramanujan's Notebooks - Berndt, B.C.; Straub, A. (Symmetry, Integrability and Geometry: Methods and Applications, 2015)
In his third notebook, Ramanujan claims the specific. In a following cryptic line, which only became visible in a recent reproduction of Ramanujan's notebooks, Ramanujan indicates that a similar relation exists if logx were replaced by log²x in the first integral and logx were inserted in the integrand of the second integral. One of the goals of the present paper is to prove this claim by contour integration. We further establish general theorems similarly relating large classes of infinite integrals and illustrate these by several examples.